Biomass to power is on the rise globally. Issue 5 (December 2015) - Kaltschmitt, Martin; Janczik, Sebastian
Abstract : The World-Market Status special report – using a variety of technologies to convert organic matter into fuel, biomass is a widely used renewable energy source in the global market. Nevertheless, the primary markets for biomass are changing, and while transport fuels stabilise, heat and electricity are increasing.